2013
DOI: 10.1111/ppa.12051
|View full text |Cite
|
Sign up to set email alerts
|

Virulence affected by assay parameters during grapevine pathogenicity studies with Botryosphaeriaceae nursery isolates

Abstract: This study assessed the symptoms that developed when 114 Botryosphaeriaceae isolates from grapevine nursery plant materials were used to inoculate excised green shoots and 1-year-old rooted canes of Sauvignon blanc. The experiments showed that all isolates and species were able to produce lesions. Overall, the Neofusicoccum species were shown to be highly pathogenic in both tissue types while the Diplodia species were highly pathogenic on canes but not on green shoots. Isolates of the most prevalent species, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Billones‐Baaijens et al . () showed that N. luteum was the predominant pathogen (57%) in nursery cuttings in New Zealand. The nursery industry in New Zealand is small, and relatively few nurseries are responsible for production and distribution of large amounts of new planting material.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Billones‐Baaijens et al . () showed that N. luteum was the predominant pathogen (57%) in nursery cuttings in New Zealand. The nursery industry in New Zealand is small, and relatively few nurseries are responsible for production and distribution of large amounts of new planting material.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Billones‐Baaijens et al . () found N. australe to comprise only 8% of infections in nursery material. In contrast to N. luteum , only 42% of the N. australe isolates clustered within group 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations